Assertions Only?. (5th September 2013) - Bronner, Ben
<x xml:space="preserve">Abstract</x> It is standardly believed that the only way to justify an assertion in the face of a challenge is by making another assertion. Call this claim assertions only. Besides its intrinsic interest, assertions only is relevant to deciding between competing views of the norms that govern reasoned discourse. assertions only is also a crucial part of the motivation for infinitism and Pyrrhonian skepticism. I suggest that assertions only is false: I can justify an assertion by drawing attention to something that clearly makes the assertion true, or likely true.